Verification of Shrinkage Formation in Steel Ingots in Laboratory Conditions - Jan Moravec; Jan Langa; Pavel Solfronk (Communications - Scientific letters of the University of Zilina, 2017)
The paper describes the process of ingot casting from a modelling material into a special ingot mould made for these tests. As a modelling material we chose stearin (tristearin, glycerol tristearate), which proved to be suitable for this kind of laboratory tests. Casting was done in two ways - using a vertical ingot mould and a horizontal one. Observation of the ingot after solidification confirmed the fact that the cavity filling took place in the laminar flow of the melt.